2012
DOI: 10.3727/096368911x600966
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Energy Loop Primes Cardiac, Neuronal, and Skeletal Muscle Differentiation in Mouse Embryonic Stem Cells: A New Tool for Improving Tissue Regeneration

Abstract: Radiofrequency (RF) waves from Wi-Fi (wireless fidelity) technologies have become ubiquitous, with Internet access spreading into homes, and public areas. The human body harbors multipotent stem cells with various grading of potentiality. Whether stem cells may be affected by Wi-Fi RF energy remains unknown. We exposed mouse embryonic stem (ES) cells to a Radio Electric Asymmetric Conveyer (REAC), an innovative device delivering Wi-Fi RF of 2.4 GHz with its conveyer electrodes immersed into the culture medium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(92 citation statements)
references
References 33 publications
(44 reference statements)
3
88
0
Order By: Relevance
“…We have recently shown that asymmetrically conveyed electromagnetic fields (ACEF) of 2.4 GHz optimize the expression of pluripotency in mouse ES cells, inducing myocardial, neuronal and skeletal muscle differentiation [74]. Similar results are obtained upon exposure to ACEF of ADhMSCs [75].…”
Section: Cancer Stem Cells: Foe or Reprogrammable Cells For Efficientmentioning
confidence: 56%
“…We have recently shown that asymmetrically conveyed electromagnetic fields (ACEF) of 2.4 GHz optimize the expression of pluripotency in mouse ES cells, inducing myocardial, neuronal and skeletal muscle differentiation [74]. Similar results are obtained upon exposure to ACEF of ADhMSCs [75].…”
Section: Cancer Stem Cells: Foe or Reprogrammable Cells For Efficientmentioning
confidence: 56%
“…Therefore, no data are available in the literature to compare the results of this study. Maioli et al [24] evaluated the effects of 2.4 GHz microwave radiation emitted from Radio Electric Asymmetric Conveyer On the other hand, in our study, motility and viability in the CE and CS groups were not statistically significant; this is in contrast with the results reported by Aweda et al [18]. He indicated that 2.4 GHz microwave radiation with 6 mW/cm² power density reduced the sperm motility and concentration, and increased the abnormal sperm cells of the male rats.…”
Section: Discussionmentioning
confidence: 99%
“…optimized the expression of pluripotency and promoted highyield commitment towards myocardial, neuronal and skeletal muscle fates in both mouse embryonic stem cells [36] and human adipose derived mesenchymal stem cells (hADSCs) [37]. Commitment towards the same lineages has been achieved by REAC treatment of human skin fibroblasts [38].…”
Section: S4mentioning
confidence: 99%
“…More recently, we discovered that radio-electric fields of 2.4 GHz, the same frequency used worldwide to connect through the Internet, could be delivered to cultured stem cells by a Radio Electric Asymmetric Conveyer (REAC) [36]. The REAC technology generates radio electric asymmetrically conveyed microcurrents in tissues, without depth limits [36].…”
Section: Stem Cells As a Target For Electromagnetic Fieldsmentioning
confidence: 99%
See 1 more Smart Citation